The effectiveness of value-added services provided by telecom companies to UPV-CM student subscribers - Dalisay, Lorena M.; Donio, Debiebon A.; Solitario, Riza Mae B.; Suson, Marivale P.; Yngson, Johann Franz G.
Executive summary - The fast-pace advent of technology is inevitable. The evolution of a simple analog cellular phone has reached the level of a one of a kind personalized gadget. This popular communication device, being hugely patronized by any type of market, from youth to adult became the main reason of telecom companies in diversifying and providing the so-called Value-Added Services (VAS). The main purpose of this is for the subscribers to have access to fun and exciting global and local information and services that suits their interests, needs and lifestyles. This study was, thus conducted to know the view of UPV-CM students about the effectiveness of Value-added services provided by the Telecom companies and to analyze the relationship of the perceived effectiveness as to the respondents' year level, allowance level, and interests. The investigation aims to ascertain if there is a difference in the effectiveness of value-added services when respondents are grouped according to year level, allowance level and interests which are being provided by two of the lading mobile services provider (Globe Telecom Co and SMART Telecommunications) as perceived by the mentioned subscribers. Descriptive method and inferential method were used to describe the nature of a situation, as it exists at the time of the study and to explore the causes of particular phenomena between the variables. The result of the study is shown on the table that follows : VARIABLES and RELATIONSHIP - Independent and Dependent : Year level - Perceive effectiveness - Significant ; Allowance level - Perceived effectiveness - Not significant ; Interest - Perceived effectiveness - Not significant. As to allowance level, there is no significant difference in the effectiveness of value-added services as perceived by UPV-CM subscribers. The availment of value-added services, which may be considered as a form of leisure, is now more widely available to the average student, regardless of allowance level. Just like other form of leisures, it is difficult to determine how much a person spend for value-added services since the choice they makes has some connection to their interests. The variable interest shows that there is no significant difference in the effectiveness of VAS as perceived by UPV-CM subscribers. This is because leisure does not have to cost money. Availing or exploring the Value-added services is just one form of satisfying a person's interest and a lot more. On the other hand, there is significant difference as to the year level. Students of UPV-CM are composed of adolescents (16-21 years old) and early adults (21-40 years old). This means that most of CM students are in their teenage years. The year level of the respondents and age of the group are significant. It is during this stage in which the person explores himself/herself by knowing his/her interests. It is also during this stage that curiosity comes in.